Late Kungurian Radioisotope Age of the Boundary Between the Balakhonka and Kolchugino Groups in the Kuznetsk Basin (Western Siberia, Russia) – Additional Evidence for the Validity of the Ufimian Stage of the East European Permian - V. V. Silantiev; Ya. M. Gutak; M. Tichomirowa; A. Käßner; L. G. Porokhovnichenko; E. V. Karasev; A. S. Felker; M. N. Urazaeva; V. V. Zharinova (Учёные записки Казанского университета: Серия Естественные науки)
This article discusses the Late Kungurian radioisotopic age (276.9 ± 0.4 Ma) of the middle part of the Starokuznetsk Formation (Kuznetsk Subgroup, Kolchugino Group) of the Kuznetsk Basin determined by chemical abrasion–isotope dilution–thermal ionization mass spectrometry (CA-ID-TIMS). The analysis of the biostratigraphic data confirms that the layer dated belongs to the interval in which the Balakhonka Flora (cordaitoid) was replaced by the Kolchugino Flora (fern-pteridosperm-cordaitoid). This indicates that the change from the Balakhonka Flora to the Kolchugino Flora in the low latitudes of Angaraland took place during the Late Kungurian. The data obtained were used for direct correlation of the lower part of the Kolchugino Group with the Upper Kungurian of the International Chronostratigraphic Chart. Similar sequences of non-marine bivalve assemblages in the Permian successions of Angaraland (giant Prokopievskia, Khosedaella-Redikorella-Palaeomutela, and dominant Palaeomutela) and Eastern Europe (giant Sinomya, Palaeomutela-Khosedaella-Redikorella, and dominant Palaeomutela) further support the validity of the correlation of the Kuznetsk Subgroup with the Ufimian Stage. The placement of the lower boundary of the Kolchugino Group in the upper part of the Kungurian Stage of the International Chronostratigraphic Scale raises the question of the continuation of the Ufimian Stage as an independent straton in the East European Stratigraphic Scale. Its lower boundary coincides with the beginning of the change in the Balakhonka and Kolchugino Flora in the low latitudes of Angaraland, as well as with the faunal exchanges between the Euramerican and Angarian non-marine bivalve assemblages.